Peningkatan Kemampuan Poetry Reading Komunitas Belajar HMJ Sastra Indonesia dan Sastra Inggris Universitas Lancang Kuning - Edward; Sorta Hutahaean; Junaidi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2020)
The title of this community service is "Increasing the Poetry Reading Ability of the Learning Community of HMJ Indonesian Literature and English Literature, Faculty of Cultural Sciences, Lancang Kuning University. The aim of this training is to provide knowledge and skills about reading English poetry to the Indonesian and English Literature HMJ community. The ability to read English poetry is both receptive and productive. Receptive because they have to understand the meaning referred to in the poetry text, and productive when doing or giving appreciation. To improve students' reading skills, it is necessary to provide training on English poetry reading techniques properly and correctly so that students gain experience and knowledge that can be used in appreciation.